Muito além do autoconsumo: as doações e transferências de alimentos nos assentamentos rurais do RS - Bellé, Adilson Roberto (2021)
The current economic model is based on the self-regulated market system. The predominant mechanism is commercial exchange, often making other economic forms such as reciprocity, donation and redistribution, coexisting in the peasantry, secondary and invisible. This thesis aimed to analyze self-consumption, transfers and food donations, as well as their purposes and socioeconomic importance in the context of rural settlements in Rio Grande do Sul, Brazil. The bibliographical review was aligned with a Polanyian perspective, on economic systems that point to reciprocity and giving as alternative economic forms that coexist with the system of mercantile exchanges. The study had mixed research methods and predominantly qualitative analysis, using exploratory research, survey and direct observation. The survey of empirical data took place between the months of May and December 2019, in three settlements: Itapuí/Meridional, Conquista do Imigrante and Ceres, with a total of sixty-five people interviewed. Through analysis of data from the Census of Agriculture (2017), it was found that 40% of all rural establishments in the country have as their main purpose their own consumption and people with family ties with the producer. Empirical data showed that 100% of the interviewed families produce for self-consumption, where the highest average values are found in those whose main economic source is the dairy activity, with a value exceeding 15 thousand reais per year, equivalent to 15 minimum wages per year. Also, it was found that more than 50% of the interviewed families have children living in the city and that they are supplied with food from the settled parents, where transfers and food donations were present to a greater or lesser degree for 88% of the interviewees , and for 60% of them it is a frequent practice. Among the most transferred or donated foods are those abundant in the production unit, especially those of animal origin, especially meat. With regard to transferred or donated amounts, it appears that the highest averages are in families that have the dairy activity and retirement as their main economic source, with an average of R$ 340.00 monthly, equivalent to 0.34 salaries monthly minimums. Retired people are the ones who most transfer or donate food, with an average of 33% of the total produced for self-consumption. In regional terms, the average amounts transferred and donated represented 0.28 monthly minimum wages in Itapuí/Meridional, 0.21 monthly minimum wages in Ceres and 0.19 monthly minimum wages in Conquista do Imigrante. Finally, it appears that in settlements with longer creation time, more attention is given to the production of food for self-consumption and, consequently, the volumes and frequency of transfers and donations from these are greater. In this sense, the production of self-consumption, transfers and food donations are important in the economic and social context of the settled family and for other people in the surroundings, whether they are family members or not, but who unite around a non-market economy moved for the gift and reciprocity still present today.